DEVELOPMENT OF DATA ANALYTIC TOOLS IN MANUFACTURING SYSTEMS USING DESIGN THINKING METHOD - Viacenza, Arraz Naoval; Setiawan, Andri D (Universitas Sahid, 2022)
Currently, it is rare for Data analytic Tools to take a user-centric approach to their users. An approach to the user is needed by collaborating between domain experts and business managers in modeling problems, finding insights, and designing models before entering the implementation phase. The objectives of this study include identifying the needs of manufacturing industry players for the application of Data Analytic Tools in the manufacturing system and providing recommendations for the application of the Design Thinking approach in developing Data Analytic models in the Manufacturing Industry. The results of this research include the manufacturing industry has a need for Data Analytic Tools to monitor and document machine performance in real time and accurately, and can help identify errors or other abnormal situations then Design Thinking can make it easier for us to design products from various user perspectives. We can understand user needs, user motivation, and user behavior towards the products we develop. Design Thinking also offers various model frameworks that can help us understand the user.